Học và làm việc với công nghệ điện tử Kỹ thuật số - Đức Minh (HCM : Thanh niên, 2010)
1. Introduction to op amps.
10. AC performance: Bandwidth, slew rate, and noise.
11. Active filters.
2. First experiences with an op amp.
3. Inverting and noninverting amplifiers.
4. Comparators and controls.
5. Selected applications of amps.
6. Signal generators.
7. Op amos with diodes.
8. Differential, instr mentation, and bridge amplifiers.
9. DC performance: bias, offsets, and driff.
Nội dung cuốn sách bao gồm
Keywords: Điện tử; Kỹ thuật số